URBAN PLANNING OF SUSTAINABLE DEVELOPMENT MODEL FOR LIBYAN CITIES - Ahmed A Elgadi; Izudinshah Abd Wahab; Lokman Hakim Ismail; Fatma Abbas; Emedya Murniwaty Samsudin (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2021)
The present sustainable metropolitan cities and the urban planning procedures in Libya are mainly aimed at reducing the impact on the environment due to the use of resources and improving life quality. Thus, the primary objective of this investigation is to create a model that focuses on reliable and valid urban planning of sustainable development, which highly reflects the Islamic way of live concerning the Libyan cities. The projected study model was tested experimentally using a review of 307 suitable samples, which included urban planning associated parties/industries, like the governmental institutions, academic research institutes, developer consultants, and planning and design engineers. Moreover, evaluations were done using the statistical software package Smart-PLS 2.0. The outcome shows that Libyan urban cities should comprise four major elements: social sustainability, environmental sustainability, economic sustainability, and institutional markers. The indicators for every element are studied in detail later in this investigation, which contributed significantly to gaining a better insight into the model for urban planning of sustainable development concerning the Libyan cities. The results provide useful insights for the urban planning industry in order to introduce the UPSD (Urban Planning of Sustainable Development) model, which is helpful as a strategy for Libyan organizations, urban planning contribution, and development to improve Libyan cities. Also, UPSD can be used to assess developed urban areas to analyze the quality of those areas and finally indicate the areas of enhancement.